Effects of Methamphetamine Abuse on Lymphocyte and Monocyte a Hematological Study - Abbas, Doaa Qasim; Jiheel, Mutashar Jaddoa; Karim, Mahdi Abdul (Journal of Science in Medicine and Life, 2025)
This study was conducted to investigate the effect of drugs on lymphocyte and monocyte The study is based on a group of addicts who were detained on charges of using narcotic substances in Wasit Governorate, where the participants were divided into two groups: the addicts group and the healthy group (as a control group). Using laboratory methods and visual observation, blood and urine samples were collected, and analyzed using a Sysmex device to determine the number of immune cells. The results of the study showed that the level of monocytes In the addicts group was insignificantly lower compared to the healthy group, while the lymphocyte level was significantly higher, indicating the effect of methamphetamine on cellular signaling pathways. The results of the statistical analysis also showed that there was a significant difference between the two groups in the levels of lymphocyte cells. These findings underscore the urgent need to understand the health effects of drug use, and highlight the importance of therapeutic interventions to reduce the risks associated with addiction. They also highlight the role of psychosocial support in helping addicted individuals recover and regain their health. Through this study, it is clear that more research is needed to understand the immune changes resulting from chronic drug use, and their potential impact on public health.